Respostas

2013-05-22T22:41:24-03:00

A= x²+12x+36=0

s=x1+x2= -b =  12  = 12  s= 12

                   a      1

 

P= x1*x2 = c  = 36 =  6 = 6    P=6

                    a      1      1

2 5 2
2013-05-23T02:00:32-03:00

A) x²+12x+36=0

 

Você utiliza a fórmula de Bhaskara.

 

∆=b²-4ac

∆=12²-4.1.36

∆=144-144

∆ =0

 

 

B) 4x²-12x+9=16

4x²-12x+9-16=0

4x²-12x-7=0

 

∆=b²-4ac

∆=(-12)²-4.4.(-7)

∆=144+112

∆=256

 

x=-b±√∆

        2a

x=-(-12)±256

         2.4

x'=12+16

        8

x'=3,5

x''=12-16

        8

x''= -0,5

ETC.

 

Espero ter ajudado!

 

 

2 5 2